Xingbi Gel Ameliorates Allergic Rhinitis by Regulating IFN-γ Gene Promoter Methylation in CD4+ T Cells via the ERK-DNMT Pathway - Ai, Si; Lin, Yueyong; Zheng, Jian; Zhuang, Xiangli (Frontiers in Surgery, 2021)
Allergic rhinitis (AR) is a common, non-infectious, chronic nasal mucosal disease primarily mediated by immunoglobulin E (IgE) following allergen exposure. Currently, studies on AR mainly focus on cytokines, IgE and its receptors, basophils, eosinophils, mast cells, and related genes. Among these, an imbalance between T helper (Th) 1 and Th2 cells is considered an important mechanism underlying AR pathogenesis. The most important cytokines in AR are interleukin (Il)-4 and interferon gamma (IFN-γ) which are secreted by Th2 and Th1 cells, respectively. Il-4 and IFN-γ are antagonistic to each other in regulating IgE synthesis. In this study, the expression of extracellular signal-regulated protein kinase (ERK) 1/2 and its phosphorylation from p-ERK1/2, were significantly increased in a cluster of differentiation of 4+ T cells of AR mice, suggesting that the ERK signaling pathway in these cells is involved in the occurrence and development of AR. This result also implies an enhanced expression of deoxyribonucleic acid methyltransferases (DNMTs). To verify the relationship between ERK signaling and DNMT expression, AR mice were treated with PD98059, a specific inhibitor of the ERK1/2 signaling pathway. The results revealed that perturbations in ERK signaling were significantly positively correlated with the downregulation of DNMT1 expression. Pharmacological intervention is key to treating AR. This study demonstrated that Xingbi gel intervention affected both serum IgE levels and AR behavior scores in mice. Based on its effects on IFN-γ gene expression, the regulation of Th1/Th2 balance, and the ERK signaling pathway, research on the effects of Xingbi gel on AR may provide new avenues in its prevention and treatment.